2018
DOI: 10.3171/2016.12.jns162478
|View full text |Cite
|
Sign up to set email alerts
|

Cyst formation after stereotactic radiosurgery for brain arteriovenous malformations: a systematic review

Abstract: OBJECTIVE Cyst formation can occasionally occur after stereotactic radiosurgery (SRS) for brain arteriovenous malformations (AVMs). Given the limited data regarding post-SRS cyst formation in patients with AVM, the time course, natural history, and management of this delayed complication are poorly defined. The aim of this systematic review was to determine the incidence, time course, and optimal management of cyst formation after SRS for AVMs. METHODS A literature review was performed using PubMed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 71 publications
0
21
1
Order By: Relevance
“…CBN after SRS has been reported mainly as a late complication after GK-based SRS for benign non-neoplastic diseases, like AVMs [ 1 ] (reported incidence: 3%). However, cases related to BMs after SRS have been scarcely reported [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CBN after SRS has been reported mainly as a late complication after GK-based SRS for benign non-neoplastic diseases, like AVMs [ 1 ] (reported incidence: 3%). However, cases related to BMs after SRS have been scarcely reported [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In non-cystic BN, conservative therapies, such as hyperbaric oxygen therapy, corticosteroids or bevacizumab, are the standard of care [ 4 , 8 , 9 ], and surgical procedures are seldom required. Conversely, CBN tends to be resistant to these conservative therapies and readily recurs, and no standard therapy has been established yet; surgical resection or continuous cyst drainage using a cystoperitoneal shunt or Ommaya reservoir placement is usually required [ 1 3 , 6 , 7 ]. According to previous reports, 32.8–88% of CBNs were symptomatic and 32.8–63% required surgery [ 1 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Late complications can include cyst formation, progressive vasogenic edema, and chronic expanding hematoma development. 16,25,26 Preliminary data from Lee and colleagues (Lee CC et al, unpublished data) have shown that the risks of adverse radiation effects are reduced if radiation exposure of intervening normal brain is minimized, especially in diffuse forms of AVMs. These authors have therefore developed, using fuzzy c-means clustering techniques, a method of separating CSF, brain tissue, and AVM vasculature on high-resolution T2-weighted images, producing color-coded maps of the AVM showing these 3 components separately in order to help guide GKSRS planning.…”
Section: Imaging Techniquesmentioning
confidence: 99%